Transcutaneous Electrical Nerve Stimulation and Neck Calliet Exercise Intervention in Cervical Root Syndrome Cases - Fazrina, Gina; Agustyaningsih, Nugraheni; Mahasih, Teki; Puspita, Wita Hana; Gunawan, Dindin Hardi; Assidqi, M Wildan (Multidiscience : Journal of Multidisciplinary Science, 2025)
Cervical Root Syndrome (CRS) is caused by spinal nerve root compression, manifesting as neck pain, sensory disturbances, and functional impairments. This study evaluates the effectiveness of combining Transcutaneous Electrical Nerve Stimulation (TENS) and Neck Calliet Exercise in managing CRS symptoms. A case study was conducted on a 52-year-old woman presenting with pain and functional limitations due to CRS. The interventions were applied in four sessions over two weeks at Ciremai Hospital, Cirebon. TENS was administered at 50-200 Hz frequency and 50-150 µs pulse duration for 15 minutes, targeting the m. splenius capitis and m. upper trapezius muscles bilaterally. The Neck Calliet Exercise included active movements, isometric contractions, and contract-relax stretching. Pain was assessed using the Visual Analogue Scale (VAS), while functional disability was evaluated with the Neck Disability Index (NDI). Post-intervention results revealed a significant reduction in pain across all neck movements, with some movements achieving complete pain resolution. Functional disability scores improved from moderate (42%) to mild (28%), demonstrating enhanced cervical mobility and motor control. These findings suggest that combining TENS and Neck callit exercise provides a synergistic approach to alleviating pain and improving functional outcomes in CRS patients.